2008
DOI: 10.1152/ajplung.90330.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endogenous GABAA channels on airway smooth muscle potentiates isoproterenol-mediated relaxation

Abstract: Emala CW. Activation of endogenous GABAA channels on airway smooth muscle potentiates isoproterenol-mediated relaxation. Am J Physiol Lung Cell Mol Physiol 295: L1040 -L1047, 2008. First published September 12, 2008 doi:10.1152/ajplung.90330.2008.-Reactive airway disease predisposes patients to episodes of acute smooth muscle mediated bronchoconstriction. We have for the first time recently demonstrated the expression and function of endogenous ionotropic GABAA channels on airway smooth muscle cells. We ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
(41 reference statements)
2
31
1
Order By: Relevance
“…Aminophylline concentration-dependently suppressed ACh-induced contraction in the present study, similar to that observed in previous reports (Karlsson & Persson, 1981;Gallos et al, 2008). However, this study shows that overdoselevels rather than clinical doses (!20 mg/mL in serum) are required to achieve a strong relaxing effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Aminophylline concentration-dependently suppressed ACh-induced contraction in the present study, similar to that observed in previous reports (Karlsson & Persson, 1981;Gallos et al, 2008). However, this study shows that overdoselevels rather than clinical doses (!20 mg/mL in serum) are required to achieve a strong relaxing effect.…”
Section: Discussionsupporting
confidence: 92%
“…To obtain concentration-response curves, aminophylline (range, 2.5-147 mg/mL) or saline (as control) were added to the organ bath at intervals of 20 min. At the end of the experiments, isoproterenol (10 mM; Sigma, Tokyo, Japan) was added; the percent relaxation by aminophylline was then calculated using the relaxation by isoproterenol as 100% (Gallos et al, 2008).…”
Section: Tracheal Tissue Preparation and Tension Recordsmentioning
confidence: 99%
“…We have previously demonstrated that ASM cells express g-aminobutyric acid A receptors (GABA A Rs), which are ligandgated chloride channels best known for their role in central nervous system (CNS) inhibitory neurotransmission, and that GABA A R agonists led to ASM relaxation (7,8). However, there is legitimate concern that the therapeutic use of GABA A R modulators to alleviate bronchoconstriction may activate CNS GABA A Rs, leading to undesirable CNS side effects.…”
mentioning
confidence: 99%
“…An emerging novel pathway to achieve bronchodilation involves modulating airway smooth muscle (ASM) chloride conductance via GABA A receptors to achieve relaxation of human precontracted ASM (15). Although there is legitimate concern that widespread activation of all GABA A receptors may lead to undesirable side effects (sedation, hypnosis, etc.…”
mentioning
confidence: 99%